Evaluation of Acid Leaching on the Removal of Heavy Metals and Soil Fertility in Contaminated Soil - Chen-Yao Chu; Tzu-Hsing Ko (Journal of Chemistry)
Heavy metal-contaminated soils were leached with various acid reagents, and a series of treatments was assessed to understand soil fertility after acid leaching. Aqua regia digestion and a five-step sequential extraction procedure were applied to determine heavy metal distribution. The average total concentrations of Zn, Cd, Cu, and Pb for contaminated soil were 1334, 25, 263, and 525 mg·kg−1 based on the ICP/AES quantitative analysis. Other than Pb extracted by H2SO4, over 50% removal efficiency of other heavy metals was achieved. A five-step sequential extraction revealed that the bound-to-carbonate and bound-to-Fe-Mn oxides were the major forms of the heavy metals in the soil. The addition of organic manure considerably promoted soil fertility and increased soil pH after acid leaching. Seed germination experiments demonstrated that after acid leaching, the soil distinctly inhibited plant growth and the addition of manure enhanced seed germination rate from 35% to 84%. Furthermore, the procedure of soil turnover after acid leaching and manure addition greatly increased seed germination rate by 61% and shortened the initial germination time. Seed germination in untreated soil was superior to that in acid-leached soil, illustrating that the phytotoxic effect of acid leaching is more serious than that of heavy metals.